Exploring flipped classroom for business English: Preliminary insights from student voices and reflections - Winantaka, Binar; Efendi, Anwar; Putro, Nur Hidayanto Pancoro Setyo (LPMPP Universitas Negeri Yogyakarta, 2025)
This study examines how undergraduate students perceive and experience the Flipped Classroom strategy in a Business English speaking course. In this model, instruction moves outside the classroom through videos and readings so that in‑class sessions are reserved for interactive activities. Although widely used in general EFL contexts, evidence of Flipped Classroom’s effectiveness in Business English, which belongs to English for Specific Purposes (ESP), is limited. The research employed a mixed‑methods design. A fourteen‑item Likert‑scale survey completed by 133 Indonesian English majors assessed perceptions of efficiency, engagement, time management and satisfaction. Semi‑structured interviews with seven volunteers provided insights on preparation, confidence, anxiety and collaboration. Students watched pre‑class videos via the university’s learning platform and participated in discussions, role‑plays and problem‑based tasks during class. The quantitative results showed positive perceptions: efficiency mean 3.91, motivation and engagement mean 3.76, time management and enjoyment mean 3.73, and satisfaction mean 4.24. Interviews highlighted that pre‑class preparation improved self‑regulated learning, boosted confidence, reduced speaking anxiety and promoted teamwork. The study’s single‑institution scope and modest sample limit generalisation; larger, diverse studies with objective measures are advised. For practice, educators should provide concise pre‑class materials, clear instructions, and adequate technological support, while designing learner‑centred, communicative classroom activities. The findings contribute to the sparse literature on Flipped Classroom in Business English and suggest its potential for enhancing communication skills and learner autonomy in professional language courses.